A Left Kidney Present With Arterial Variation: A Case Report - Mohammed A A Abdelmotalab; Abobaker Elhmody (Negah Institute for Scientific Communication, 2022)
Introduction: Renal vasculature variations were normally found. Awareness of this variation was helpful in many clinical field procedures during the routine dissection of the posterior abdominal wall of approximately a 67-year-old male formaldehyde cadaver.. Case Report: The left kidney presents with an arterial variation. An accessory renal artery was detected from the lateral aspect of the abdominal aorta at the level disc between L2 and L3, just above the origin of the inferior mesenteric artery on the left side. Conclusion: Knowledge of anatomical variation of the renal arteries has clinical significance in renal transplantation procedures and for interventions in angiography.